The COVID-19 economic crisis in Mexico through the lens of a financial conditions index - Julio A. Carrillo; Ana Laura García (Banco de México, 2021)
The COVID-19 pandemic not only generated real shocks affecting economic activity severely, but also a broad uncertainty that unleashed an extreme shock to financial markets. In this paper, we focus on the financial dimension of the pandemic from the viewpoint of an emerging market economy. Accordingly, we estimate a financial conditions index for Mexico since 1993 and find that the acute turmoil generated by the pandemic stands among the four largest episodes of financial distress experienced by the country. In addition, we find evidence suggesting that real variables have responded differently to shocks that worsen financial conditions than to shocks that improve them
Keywords: C11; C32; E44; G01; 330; COVID-19; financial conditions; emerging-market economy; local projections